Etiological profile of pyodermas in a tertiary care hospital in North-East India and their antibiotic sensitivity pattern - Devi, Bijayanti; Das, Kamal; Gupta, Suman (International Journal of Research in Dermatology, 2019)
Background: Hypermelanoses involving predominantly the face and the neck is relatively common and often presents a complex diagnostic problem. The present study was done in the study population of 500 patients of facial pigmentation, attending the skin outpatient department in AarupadaiVeedu Medical College and Hospital from October 2015 to September 2017. Aim and objective of the study was to study various clinical patterns of facial pigmentation, their clinical characteristics, their association with other pigmentary disorders and to evaluate the different etiotogical and precipitating factors. Methods: In this study, a special proforma was prepared. Patients were thoroughly interviewed and examined to find out dermatological and systemic diseases and they were subjected to investigations to evaluate different etiological factors and diagnose the clinical type of facial pigmentation. Results: The present study showed a strong female preponderance. Among the total study population there were 55% cases of melasma, 20% cases of Riehls melanosis, 10% cases of periorbital pigmentation and 5% of miscellaneous causes. Conclusions: Facial pigmentation was commonly seen in the females. 21-30 years age group was the most commonly affected age group in all types of facial pigmentation. Melasma, Riehls melanosis and periorbital pigmentation were the most common clinical types of facial pigmentation observed.